Body-mass index, blood pressure, and cause-specific mortality in India: a prospective cohort study of 500 810 adults - Vendhan Gajalakshmi, PhD; Ben Lacey, DPhil; Vendhan Kanimozhi, FRCR; Paul Sherliker, BA; Richard Peto, ProfFRS; Sarah Lewington, DPhil (The Lancet Global Health, 2018)
Summary: Background: The association between cause-specific mortality and body-mass index (BMI) has been studied mainly in high-income countries. We investigated the relations between BMI, systolic blood pressure, and mortality in India. Methods: Men and women aged 35 years or older were recruited into a prospective study from the general population in Chennai, India between Jan 1, 1998, and Dec 31, 2001. Participants were interviewed (data collected included age, sex, education, socioeconomic status, medical history, tobacco smoking, and alcohol intake) and measured (height, weight, and blood pressure). Deaths were identified by linkage to Chennai city mortality records and through active surveillance by household visits from trained graduate non-medical fieldworkers. After the baseline survey, households were visited once in 2002–05, then biennially until 2015. During these repeat visits, structured narratives of any deaths that took place before March 31, 2015, were recorded for physician coding. During 2013–14, a random sample of participants was also resurveyed as per baseline to assess long-term variability in systolic blood pressure and BMI. Cox regression (standardised for tobacco, alcohol, and social factors) was used to relate mortality rate ratios (RRs) at ages 35–69 years to systolic blood pressure, BMI, or BMI adjusted for usual systolic blood pressure. Findings: 500 810 participants were recruited. After exclusion of those with chronic disease or incomplete data, 414 746 participants aged 35–69 years (mean 46 [SD 9]; 45% women) remained. At recruitment, mean systolic blood pressure was 127 mm Hg (SD 15), and mean BMI was 23·2 kg/m2 (SD 3·8). Correlations of resurvey and baseline measurements were 0·50 for systolic blood pressure and 0·88 for BMI. Low BMI was strongly associated with poverty, tobacco, and alcohol. Of the 29 519 deaths at ages 35–69 years, the cause was vascular for 14 935 deaths (12 504 cardiac, 1881 stroke, and 550 other). Vascular mortality was strongly associated with systolic blood pressure: RRs per 20 mm Hg increase in usual systolic blood pressure were 2·45 (95% CI 2·16–2·78) for stroke mortality, 1·74 (1·64–1·84) for cardiac mortality, and 1·84 (1·75–1·94) for all vascular mortality. Although BMI strongly affected systolic blood pressure (an increase of about 1 mm Hg per kg/m2) and diabetes prevalence, BMI was little related to cardiac or stroke mortality, with only small excesses even for grade 1 obesity (ie, BMIs of 30·0–35·0 kg/m2). After additional adjustment for usual systolic blood pressure, BMI was inversely related to cardiac and stroke mortality throughout the range 15·0–30·0 kg/m2: when underweight participants (ie, BMI 15·0–18·5 kg/m2) were compared with overweight participants (ie, BMI 25·0–30·0 kg/m2), the blood-pressure-adjusted RR was 1·28 (95% CI 1·20–1·38) for cardiac mortality and 1·46 (1·22–1·73) for stroke mortality. Interpretation: In this South Asian population, BMI was little associated with vascular mortality, even though increased BMI is associated with increased systolic blood pressure, which in turn is associated with increased vascular mortality. Hence, some close correlates of below-average BMI must have important adverse effects, which could be of relevance in all populations. Funding: UK Medical Research Council, British Heart Foundation, Cancer Research UK.